(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2014)
In the articles heroes characters of М. Slaboshpytskyi biographic novels, prin-ciples of their behavior, moral and spiritual values, feelings, influenced reflections of personages, difficult heartfelt conflicts and contradictions, their tense psychological problems, causes and effects of psychical derangements are marked.